2006
DOI: 10.1080/08958370500516291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subchronic Inhalation Toxicity of Dimethyl Disulfide in Rats

Abstract: This study was carried out to investigate the potential subchronic inhalation toxicity of dimethyl disulfide (DMDS) via whole-body exposure in F344 rats. Groups of 10 rats of each sex were exposed to DMDS vapor by whole-body exposure at concentrations of 0, 5, 25, or 125 ppm for 6 h/day, 5 days/wk for 13 wk. All the rats were sacrificed at the end of treatment period. During the test period, clinical signs, mortality, body weights, food consumption, ophthalmoscopy, urinalysis, hematology, serum biochemistry, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…Previous studies demonstrated that the function and weight of adrenal glands is adversely effected by various stressful factors. [53][54][55][56] So the increased weights of adrenal glands are also considered to be related to stress responses, induced by the administration of ZnO SM20(+) NPs, which is consistent with the decreased body-weight gain in the group.…”
supporting
confidence: 58%
“…Previous studies demonstrated that the function and weight of adrenal glands is adversely effected by various stressful factors. [53][54][55][56] So the increased weights of adrenal glands are also considered to be related to stress responses, induced by the administration of ZnO SM20(+) NPs, which is consistent with the decreased body-weight gain in the group.…”
supporting
confidence: 58%
“…In the second inhalation study, rats were exposed for 13 weeks to 5, 25, or 125 ppm (0.02, 0.10, or 0.48 mg/L) DMDS for 6 hours/d. 88 A treatment-related decrease in body weight gain, food consumption, and thymus weight was observed along with an increase in adrenal gland weight. Histopathology did not reveal any increase in the incidence or severity of abnormal tissue alterations relative to controls.…”
Section: International Journal Of Toxicology 33(supplement 1)mentioning
confidence: 98%
“…The significant decrease in the absolute and relative weights of the thymus is considered to be related to the cold stress responses induced by the continuous exposure to a concrete building environment because it was associated with the increased incidence of clinical signs and slightly increased adrenal weight. Previous studies reported that various stress factors adversely affect the function and weight of the thymus and adrenal glands (Kim et al, 2006;Kioukia-Fougia et al, 2002;Odio and Maickel, 1985;Ulrich-Lai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%